Pengaruh Gaya Hidup, Brand Image, Brand Trust, Dan Brand Awareness Terhadap Keputusan Pembelian Produk Sepatu Ventela : (Studi Kasus Mahasiswa FEBI UIN Gusdur Angkatan 2020) - Baqiyatus Sholikhah; Dwi Novaria Misidawati (Universitas 45 Surabaya, 2024)
In this modern era, shoes have become an important need for every individual, because they are not only used for sports but have become a fashion trend to support their appearance. Apart from that, shoes have also become a favorite among shoe lovers. The development of the shoe industry in Indonesia is increasing rapidly from year to year, resulting in the emergence of new companies. One shoe product that experiences intense competition in the industrial world is the Ventela company. This research discusses the influence of lifestyle, brand image, brand trust and brand awareness on purchasing decisions for Ventela shoes. This research was conducted to analyze the influence of lifestyle, brand image, brand trust, and brand awareness on purchasing decisions for 2020 FEBI UIN Gusdur students, both partially and simultaneously. This type of research is a survey with a quantitative approach. The population of this research is FEBI UIN Gusdur Students Class of 2020. The sampling used was non-probability sampling with accidental sampling technique so that a sample of 80 respondents was obtained. The research results show that lifestyle has no influence on purchasing decisions, brand image influences purchasing decisions, brand trust influences purchasing decisions, and brand awareness influences purchasing decisions.